(untitled) (Gilgameš, 2019)
This paper was born from a field research started in 2015 in Mexico City, where I got to know the work of the artists presented: Torolab, Nortec Collective and Rubén Ortiz Torres. They have in common a link with the Mexico/USA border, to which they relate in different ways and for different reasons. The first paragraphs of the paper are meant to outline a theoretical introduction to the theme of the border, which is followed by a study on the generative potential of the border areas. The central focus of the research is an excerpt of the interviews and studio visits carried out as part of a trip undertaken in August 2016, to meet the artists already mentioned and the cross-border dynamics in person: from Tijuana (Baja California, Mexico) to Los Angeles (California, USA), walking through the border. What emerges is a portrait of the frontier region as a laboratory of globalization, where contrast, hybridization and cultural exchange make innovation move faster. In this context, the work of the artists presented demonstrates the potential of art as an engine of urban regeneration, cultural integration and social transformation.